Ideological Fantasy of an Indonesian Absurdist in Danarto’s Short Story Godlob - Asep Anugrah (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2019)
Reasoning about ideological criticism through literary work can be seen from how the literary work represents the ideology of the author as a critical form of social dominated ideology. The matter is when the criticism exactly shows paradox with what the author delivered, so the type of ideological criticism has been described by the author with real literary work which uses language as a medium. Therefore, the author's subjectivity of literary work is just symbolization which forms as post-ideology and it is termed by Žižek as cynicism which only appears on the level of ideological fantasy. This matter is applied by the researcher to analyze Danarto’s short story Godlob. This research focuses on Danarto’s ideology which is offered as radical acts by the characters. This research method leads to textual and objective analysis to detect radical action in Godlob Short Story. The result of the textual analysis is presented with the subjectivity of the author, which produces harmony as well as the paradox of radical action. This is what described in the discourse of Danarto's short story Godlob about; (1) how the radical actions of the characters are depicted in the Godlob short story, and (2) how ideological fantasies are generated through the encounter of both literary subjects in the Godlob short story. The goal is to see that ideological criticism through literary works is not only through the phenomenon but also through the reality itself. In other words, by analyzing radical action textually and then confronted with the author's subjectivity, the paradox of ideological criticism can be embedded in the discourse of this study. Based on the analysis, literary works as a criticism shows how ideological fantasy comes as a result of the cynicism of the author. Danarto seemed to be immersed in an ideology that he criticized in his work.